REVITALIZATION OF ISLAMIC EDUCATION IN UNIVERSITY THROUGH ACTIVE LEARNING STRATEGY BASED ON SOCIAL PROBLEMS - Kholidah, Lilik Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
In the structure of Indonesian higher education curriculum, Islamic education holds an important role in transforming values which based on Islamic dogma to form student's personality with character. Understanding and appreciation of the good values of Islamic teachings will encourage internal awareness of students in carrying out life activities in accordance with the basic values of Islamic teachings. Unfortunately the implementation of Islamic education learning in university until now is assumed still experiencing many weaknesses. In practice, Islamic education still emphasizes the paradigm of transfer of knowledge, less attention to its relevance to the problems of life. It tends to pay attention to the cognitive aspects and there is less space for fostering affective aspects. On that basis, amid the global challenge and the rapid flow of social life change, revitalization of Islamic education is considerably important Active learning strategy based social problem solving, very important applied in Islamic education. This is because in the process of learning and completion, students may gain experience using the knowledge and skills that have been owned to apply to problem solving.